Geometry curvature influence on melting and solidification performance in nano particle added phase change material to storage energy - Kiyak, Burak; Biswas, Nirmalendu; Öztop, Hakan Fehmi; Selimefendigil, Fatih (Elsevier, 2025)
This research explores the combined impact of geometric curvature and nanoparticle-enhanced phase change materials (PCMs) on the performance of thermal energy storage (TES) systems. Two geometrical configurations-curved and straight-are analysed under nine distinct heating and cooling setups, using paraffin-based PCM (RT18HC) mixed with copper (Cu) nanoparticles at concentrations ranging from 0 % to 4 %. The finite volume-based numerical simulations technique utilized an enthalpy-porosity method to investigate the melting and solidification behavior during a 450 min thermal cycle. The results quantitatively demonstrate that curved geometries significantly improve natural convection, enhancing the heat transfer during melting and solidification process. For example, curved geometries, combined with 4 % Cu nanoparticle-enhanced PCM, significantly improved heat transfer, reducing phase change times by 35 % and 47 % compared to straight configurations. Additionally, the Curved Right design achieved up to a 50 % improvement in energy discharge efficiency. The enhanced natural convection within the curved structures reduces melting times by up to 46.2 %, outperforming the conduction-driven heat transfer in straight geometries. The reduced thermal gradients and uniform phase changes process allows rapid thermal cycling. In contrast, pure PCM without nanoparticles shows slower melting and prolonged solidification rate, which highlights its thermal limitations. The present study reveals that the combination of curved geometries with nanoparticle-enhanced PCMs significantly improves the efficiency of TES by accelerating the phase transitions through enhanced free convection and thermal conductivity. These understandings contribute to the optimization of energy storage designs for industrial and renewable energy-based applications.
Keywords: Curved geometry; Phase change material (PCM); Melting and solidification process; Thermal behavior; Heat transfer